2014
DOI: 10.1128/jvi.00481-14
|View full text |Cite
|
Sign up to set email alerts
|

Host MicroRNA Regulation of Human Cytomegalovirus Immediate Early Protein Translation Promotes Viral Latency

Abstract: Reactivation of human cytomegalovirus (HCMV) is a significant cause of disease and death in immunocompromised patients, underscoring the need to understand how latency is controlled. Here we demonstrate that HCMV has evolved to utilize cellular microRNAs (miRNAs) in cells that promote latency to regulate expression of a viral protein critical for viral reactivation. Our data reveal that hsa-miR-200 miRNA family members target the UL122 (immediate early protein 2) 3= untranslated region, resulting in repression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 56 publications
(58 reference statements)
1
94
0
3
Order By: Relevance
“…73 Overexpression of the miR-200 cluster decreases HCMV titers in fibroblasts, 74 and miR-200 levels were high in latently infected CD34 þ cells and in persistently infected monocytes, but not in lytically infected macrophages. 75 In addition, miR-200 family members target HCMV UL122 3 0 untranslated region, inhibiting IE2 translation, 75 and target Sec23a, which is involved in endoplasmic reticulum-toGolgi vesicle transport and could modulate VAC formation. 76 Interestingly, miR-200 was expressed in HCMVinfected AmEpCs and increased late in persistent infection (T.T., unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…73 Overexpression of the miR-200 cluster decreases HCMV titers in fibroblasts, 74 and miR-200 levels were high in latently infected CD34 þ cells and in persistently infected monocytes, but not in lytically infected macrophages. 75 In addition, miR-200 family members target HCMV UL122 3 0 untranslated region, inhibiting IE2 translation, 75 and target Sec23a, which is involved in endoplasmic reticulum-toGolgi vesicle transport and could modulate VAC formation. 76 Interestingly, miR-200 was expressed in HCMVinfected AmEpCs and increased late in persistent infection (T.T., unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular viral genomes were quantified by qPCR as described previously (37). Viral genomes were detected using primers directed at UL123 ( Table 2).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…To determine the contribution of US28 toward a successful latent infection of Kasumi-3 cells, we assessed the production of extracellular virions over a 5-day time course following latent infection of Kasumi-3 cells and assessed viral DNA using qPCR (37). The cells infected with either the US28⌬ or all⌬ virus yielded an increase in extracellular viral genomes (Fig.…”
Section: Us28 Is Required For Latent Infection In Kasumi-3 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This virus overlaps the binding site of cellular miRNA, miR-373 (122,123). Due to the presence of adjacent sites for miR-433a and miR-367a in MICB mRNA, interaction between viral miR-UL112 and cellular miR-376a is feasible, which leads to silencing of MICB expression in a human cytomegalovirus-infected person (124,125). It has also been shown that expression of two miRNAs, miR-429 and miR200b, regulates entry to the lytic phase of Epstein-Barr virus by suppressing expression of ZEB1 and ZEB2.…”
Section: Viral Microrna-mediated Response In Therapeuticsmentioning
confidence: 99%